From High School Access to Postsecondary Success: An Exploratory Study of the Impact of High-Rigor Coursework - T. Lee Morgan; Diana Zakhem; Wendy Loloff Cooper (MDPI AG, 2018)
Educators and policymakers are keenly aware of the need to prepare students to compete in an increasingly global society. It is widely accepted that a high school diploma is not sufficient and that secondary schools have a responsibility to prepare students to be college and career ready. This study examined participation in a rigorous secondary curriculum and the corresponding outcomes related to college enrollment, persistence, and graduation. Focusing on the involvement of students in high-rigor courses that provide a stronger pathway to college, we seek to understand further the indicators that lead to postsecondary success. The sample comprises 1464 students who graduated from high school between 2009 and 2014. The primary analytic technique was binary logistic regression. The results from this study confirmed that a positive relationship exists between high-rigor courses and college success. This relationship was evident even after controlling for relevant student demographics including gender, ethnicity, and socioeconomic status. The academic benefits of the high-rigor course participation are discussed.